If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(y + 9) = 3y + 17 Reorder the terms: -7(9 + y) = 3y + 17 (9 * -7 + y * -7) = 3y + 17 (-63 + -7y) = 3y + 17 Reorder the terms: -63 + -7y = 17 + 3y Solving -63 + -7y = 17 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -63 + -7y + -3y = 17 + 3y + -3y Combine like terms: -7y + -3y = -10y -63 + -10y = 17 + 3y + -3y Combine like terms: 3y + -3y = 0 -63 + -10y = 17 + 0 -63 + -10y = 17 Add '63' to each side of the equation. -63 + 63 + -10y = 17 + 63 Combine like terms: -63 + 63 = 0 0 + -10y = 17 + 63 -10y = 17 + 63 Combine like terms: 17 + 63 = 80 -10y = 80 Divide each side by '-10'. y = -8 Simplifying y = -8
| 3/4c-0.11=0.23(c-5) | | -32+6d=-7(8d-5) | | 2=-8x+5(x-2) | | F(x)=-8x+9 | | r-8.3=-7.8 | | a=1/2*28*18 | | 4.3+x=6.7 | | Log(x+8)+6=8 | | -4+2(1+3n)=-25 | | 6d-7-(3-4d)= | | 3a=a+23 | | 3+24(2.5x+x)= | | x+2x+9=0 | | 4x-44=76+8x | | 5(5x+3)=3(8x+(-2))+4 | | 20k+30=14k-90 | | (2x+8)(2x-5)=0 | | 6(n-6)=(n+2) | | 10x-8y=-6 | | 3n+2n+6n=(3+2+6)n | | 4x-130=134-8x | | -8y+5(y+4)=5 | | 35h-720=1000 | | 3x-2+2(2+4x)= | | 35h-1000=720 | | F(x)=3-5x/7 | | -88-12x=143-x | | 6(2n)+3(r+2)= | | F(x)=3-5x/ | | -x-39=13+2x | | X^2-73x+210=0 | | 1x+(3-x)=1x+5 |